Climatic variables limit population abundance of Neoleucinodes elegantalis: Important neotropical tomato pest. (December 2020) - Silva, É.M.; Silva, R.S.; Gontijo, P.C.; Rosado, J.F.; Bacci, L.; Martins, J.C.; Picanço, M.C.
Abstract: The small tomato borer, Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae), is a significant pest of tomato crops in Central and South America, where its occurrence and abundance is dependent on environmental factors. The aim of this study was to determine the effects of climate variables on the abundance of N. elegantalis in open-field tomato cultivation. The population density of N. elegantalis was sampled weekly after tomato fruits reached a diameter ≥0.5 cm until the final harvest, over 15 commercial tomato fields. Egg abundance and mortality, larval abundance and mortality, and pupae abundance was determined within each sample. Rain, photoperiod, wind speed, temperature, and relative humidity was monitored daily. The highest densities of N. elegantalis eggs, larvae, and pupae occurred between March and July. After July, N. elegantalis density was drastically reduced. Path analysis revealed that temperature, rainfall, and photoperiod had a significant and direct effect on N. elegantalis egg abundance, which indirectly affected larval and pupal densities. The path coefficient indicated a negative correlation between the number of N. elegantalis eggs and the photoperiod, while air temperature and rainfall had a positive effect on theses densities. This study improves our understanding of how climate influences N. elegantalis population dynamics. This information will assist in the development of more sustainable pest-management programs for tomato fields, allowing farmers to monitor and adopt control methods when populations rise. Highlights: Positive effects of temperature and rainfall on Neoleucinodes elegantalis. Temperature, rainfall, and photoperiod influence N. elegantalis egg numbers. The increase of photoperiod was detrimental to the number of N. elegantalis eggs. Temperature increases provided favorable conditions for N. elegantalis. Rainfall increases provided favorable conditions for N. elegantalis.